(3GdJehjd hhXGFaI aj GdHfhc GdESdGejI hGdJLGQjI (B:s (3OQGSI ebGQfI (B/s - (3GdYGfj, bJjHI YHO GdQMefs ((3YeGf(B: s (3OGQ GdfaGFS ddfTQ hGdJhRjY(B, s, 2013)
(3WHjYI GdJehjd hhXGFag aj GdHfhc GdESdGejI hGdJLGQjI(B- (3WHjYI GdJehjd hhXGFag aj GdHfhc(B- (3CSGdjH GdJehjd GdeSJNOeI aj GdHfhc GdESdGejI(B- (3COhGJ GdJehjd GdeSJNOeI aj GdHfhc GdESdGejI(B- (3GdNOeGJ GdeUQajI GdJehjdjI(B- (3GdNOeGJ GdeUQajI(B- (3GdeYGedGJ GdeGdjI GdeYGUQI(B- (3GdeDSSGJ hGdCShGb GdeGdjI(B- (3Jbjje GdSjGSGJ GdJehjdjI ddHfhc GdESdGejI hGdJLGQjIs
(3GdeQGLY U(B.429s
Keywords: (3GdHfhc GdESdGejIs; (3GdJHGOd GdJLGQjs; (3GdJehjds